2020
DOI: 10.1016/j.heliyon.2020.e05827
|View full text |Cite
|
Sign up to set email alerts
|

Using stakeholders' preference for ecosystems and ecosystem services as an economic basis underlying strategic conservation planning

Abstract: Ecosystem services (ES), commonly defined as the benefits people get from ecosystems, are key components in improving human well-being. However, as land utilization transitions from forest and agricultural land to urban areas and industrial complexes, the continuous provision of ES is affected. To ensure sustainable development, conservation programs should be implemented that consider both the stakeholders' well-being while also maintaining ecosystem health and integrity. Consequently, to improve the strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…This transition emphasised the interdisciplinary features of landscape planning, which combines the natural and social sciences to accomplish sustainable development and, therefore, enhance human well-being. Recent studies have also highlighted the issue of trade-offs, noting that failure to account for the perspectives of various stakeholders can result in misaligned policy implementation [84].…”
Section: Dynamic Development Of Research Topicsmentioning
confidence: 99%
“…This transition emphasised the interdisciplinary features of landscape planning, which combines the natural and social sciences to accomplish sustainable development and, therefore, enhance human well-being. Recent studies have also highlighted the issue of trade-offs, noting that failure to account for the perspectives of various stakeholders can result in misaligned policy implementation [84].…”
Section: Dynamic Development Of Research Topicsmentioning
confidence: 99%
“…Las lagunas nos brindan distintos servicios ecosistémicos por la presencia de una gran biodiversidad. [2], a pesar de ello, las actividades antropogénicas han ido vulnerando dichos ecosistemas, destruyendo los bienes y servicios de los recursos lagunares [3]; sin tener en cuenta que son esenciales para que los seres vivos se desarrollen en un ambiente sostenible [4].…”
Section: Introductionunclassified
“…Agricultural and environmental stakeholders prioritize ecosystem services differently depending on values, knowledge and experience. Ureta et al (2020) concluded that residents living further away from water bodies with insufficient water quality prioritize other ecosystem services. In order to preserve the values that are important to the wide range of stakeholders, it is necessary to focus on multi-functionality as a shared goal in addition to seeking local land use solutions (Hölting et al, 2020).…”
Section: The Challenges Of Today and Tomorrowmentioning
confidence: 99%